2015
DOI: 10.1007/s00038-015-0698-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease among people with drug use disorders

Abstract: Patients injecting drugs using prescribed methadone were at elevated risk for cardiovascular disease and should be monitored for CVD. Opioid medications should be evaluated in terms of their cardiovascular sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Some of the main somatic problems previously reported for this population in Norway have been hepatitis C, liver failure, cancer, kidney and lung disease [11,12]. A recent Danish study reported an earlier onset of cardiovascular disease among hospitalized drug users compared to the general population [13], and it is likely that OMT patients also experience many other somatic problems at higher rates and at relatively young ages. Sexual dysfunctiona common side effect of OMT medications as well as associated with ageingwas also a common complaint among OMT patients according to a meta-analysis, although the authors noted that differences in sample ages prevented proper comparisons, and only men were included [14].…”
Section: Introductionmentioning
confidence: 79%
“…Some of the main somatic problems previously reported for this population in Norway have been hepatitis C, liver failure, cancer, kidney and lung disease [11,12]. A recent Danish study reported an earlier onset of cardiovascular disease among hospitalized drug users compared to the general population [13], and it is likely that OMT patients also experience many other somatic problems at higher rates and at relatively young ages. Sexual dysfunctiona common side effect of OMT medications as well as associated with ageingwas also a common complaint among OMT patients according to a meta-analysis, although the authors noted that differences in sample ages prevented proper comparisons, and only men were included [14].…”
Section: Introductionmentioning
confidence: 79%
“…The European Monitoring Centre for Drugs and Drug Addiction (18), in Europe, and the National Institute on Drug Abuse (20), in US, first sounded the alarm, raising concerns about the vulnerability of people with substance use disorders to COVID-19, especially because of opiates (e.g. heroin), synthetic opioids, and methamphetamine effects on the respiratory system and pulmonary health (21)(22)(23). Comorbidities, including cardiovascular and other respiratory diseases, have proven to worsen prognosis in patients with other coronaviruses affecting the respiratory system, such as SARS-CoV and MERS-CoV (24).…”
Section: Covid-19 Health Risks Associated To Psychotropic Drug Usementioning
confidence: 99%
“…The Norwegian health authorities [9] recommend exercise as an adjunct treatment for substance use disorders because, in addition to clinical benefits, it is cost-effective and accessible after the formal treatment system. Importantly, exercise reduces the risk of numerous preventable chronic diseases [10,11], of which people with substance use disorders already experience earlier and with more fatal consequences [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%